Sensitivity and specificity of screening tools for postpartum depression: a systematic review - Che Abdullah, Azreena; Zulkefli, Nor Afiah Mohd; Minhat, Halimatus Sakdiah; Baharom, Anisah; Ahmad, Norliza (Persatuan Pakar Perubatan Kesihatan Awam Malaysia,Malaysian Public Health Physicians Association, 2019)
Postpartum depression is a depressive episode that can start at any point during the first year after childbirth. There are several tools that can be used for PPD screening. The need to define a predictive tool that is clinically useful and has acceptable sensitivity and sensitivity is important especially to be used in the primary care setting. This systematic review investigates the evidence of the sensitivity and specificity of screening tools used for PPD screening. The Standard for Reporting of Diagnostic Accuracies (STARD) guidelines were used to conduct the review as a basis for our methodology. PubMed, ScienceDirect and Springerlink databases between 2007 until 2017 were comprehensively searched EPDS and BDI instrument has sensitivity of more than 80% but findings for specificity was inconclusive. The heterogeneity across studies could be the result of methodological differences in validation of the instruments. In addition, these studies were conducted across continents and settings with different cultures, languages and resources. We have identified 5 different instruments used to screen for postpartum depression. The EPDS was the most validated instrument in the review and we found that EPDS and BDI have higher accuracy to screen postpartum depression because the sensitivity reported were more than 80%.